Downbeat nystagmus in association with the dorsal midbrain syndrome: proposed mechanisms, literature review, and case series - Saab, Lea; Eggenberger, Eric R.; Cho, Catherine; Friedrich, Maximilian U.; Rucker, Janet C. (Frontiers in Neurology, 2025)
IntroductionDownbeat nystagmus (DBN) is classically attributed to cerebellar pathology. Far less often, DBN arises from brainstem disease, with midbrain etiologies being exceptionally rare and poorly characterized. In particular, DBN with the dorsal midbrain syndrome has been sporadically reported and its mechanism is unclear.Methods/resultsWe analyzed non-human primate and human literature on vertical gaze and brainstem-related DBN in the context of three patients with DBN and dorsal midbrain syndrome. Upgaze paresis was universal, skew deviation present in two, and parkinsonism developed in two after shunt-related complications. We reviewed the literature using strict criteria requiring DBN in central gaze and at least two definitive features of the dorsal midbrain syndrome, identifying two additional patients.DiscussionIn five patients with DBN and dorsal midbrain syndrome, aqueductal stenosis or compression with upgaze paresis were unifying features. Potential mechanisms for DBN include involvement of the interstitial nucleus of Cajal, disruption of descending midbrain projections to paramedian tracts, or unstable cerebellar outflow, but clinical and experimental evidence makes these explanations less compelling. Converging evidence from our series, prior reports, and non-human primate studies suggests bilateral posterior commissural dysfunction related to aqueductal pathology as the most plausible mechanism for DBN with the dorsal midbrain syndrome.